Association between phase angle and daily creatinine excretion changes in critically ill patients: an approach to muscle mass - Vargas-Errázuriz, Patricio; Dreyse, Natalia; López, René; Cano-Cappellacci, Marcelo; Graf, Jerónimo; Guerrero, Julia (Frontiers in Physiology, 2025)
Assessing muscle mass in critically ill patients remains challenging. This retrospective cohort study explores the potential of phase angle (PA°) derived from bioelectrical impedance analysis (BIA) as a surrogate marker for muscle mass monitoring by associating it with daily creatinine excretion (DCE), a structural and metabolic muscle mass marker. In 20 ICU patients, we observed a linear relationship between PA° and DCE at initial (S1) and follow-up (S2) points, with Rho values of 0.78 and 0.65, respectively, as well as between their percentage changes (Rho = 0.80). Multivariate analysis confirmed a strong association between changes in PA° and DCE (adjusted R2 of 0.73), while changes in the extracellular water to total body water (ECW/TBW) ratio showed no significant association. This study establishes a relationship between a BIA-derived independent-weight parameter and DCE, highlighting the potential of PA° for muscle mass monitoring during acute changes, such as those seen in ICU settings. Integrating PA° into clinical practice could provide a non-invasive and reliable tool to enhance muscle assessment and support targeted interventions in critically ill patients.